Radiation, a two-edged sword: From untoward effects to fractionated radiotherapy - Chew, Ming Tsuey *; Jones, B.; Hill, M.; Bradley, D.A. (Elsevier, 2021)
Radiations in medicine cover a wide range of applications, predominantly in diagnostic imaging and radiotherapy, encompassing photons (x- andγ-rays) and particle radiation, as well as with the use of liquid sources in nuclear medicine focusing on physiological functional imaging, tumour detection or targeted radiotherapy. The biological interactions of ionizing radiation leads naturally to questions of beneﬁts and risk following dose exposures. The inherent properties of ionizing radiation in sterilising dividing cells can oﬀer immense beneﬁts withrespectto tumourcontrol,butradiationcanalsodeliverpotentialharminthe formofnormaltissue toxicity or carcinogenesis. The advances in radiation technology, oﬀering accurate and reliable dose delivery, in concert with greater understanding of the underpinning radiobiological eﬀects are creating an ever-growing ability to extract maximum beneﬁt and minimise risk. The radiobiological eﬀects fall broadly under the headings of mutagenesis, chromosomal aberrations, radiation induced genomic instability and cell death. The enormity of evidence derived from these underlie the mechanism of the six Rs of controlled radiotherapy: repair, repopulation, reoxygenation, redistribution, radiosensitivity and most recently, remote bystander cellular eﬀects (including low dose hyper-radiosensitivity, adaptive response, hormesis, abscopal eﬀect and immune response). Herein, we seek to discuss how such understanding leads to optimised radiotherapy.